1989
DOI: 10.1002/hep.1840100608
|View full text |Cite
|
Sign up to set email alerts
|

The Rat Liver Microcirculation in Alcohol–Induced Hepatomegaly

Abstract: It has been suggested that hepatocyte enlargement can lead to compression of the extracellular space (sinusoidal and interstitial) and induce portal hypertension. However, this hypothesis has never been tested by measuring the vascular and extravascular spaces in the intact liver. The aim of the present study was to investigate the effects of chronic alcohol intake on the hepatic microcirculation using Goresky's multiple-indicator dilution technique in the isolated perfused rat liver. Female rat littermates we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

1990
1990
2012
2012

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Prolonged hypoxia has been reported to cause mitochondrial dysfunctions through producing reactive oxygen species, impairing mitochondrial fatty acid oxidation and in turn stimulating lipid synthesis in the ethanol-treated liver [1]. These hypoxic alterations with continuous ethanol consumption accelerate fat infiltration into hepatocytes and lead to a dramatic increase in the size of hepatocytes [4]. As a consequence of impairment of hepatic microcirculation, presumably due to mechanical oppression by swollen hepatocytes and increased sinusoidal contractility of non-parenchymal cells in response to constrictors such as endothelin-1 [5], hypoxic damage processes and fat accumulation might further be exacerbated concomitantly.…”
Section: Introductionmentioning
confidence: 99%
“…Prolonged hypoxia has been reported to cause mitochondrial dysfunctions through producing reactive oxygen species, impairing mitochondrial fatty acid oxidation and in turn stimulating lipid synthesis in the ethanol-treated liver [1]. These hypoxic alterations with continuous ethanol consumption accelerate fat infiltration into hepatocytes and lead to a dramatic increase in the size of hepatocytes [4]. As a consequence of impairment of hepatic microcirculation, presumably due to mechanical oppression by swollen hepatocytes and increased sinusoidal contractility of non-parenchymal cells in response to constrictors such as endothelin-1 [5], hypoxic damage processes and fat accumulation might further be exacerbated concomitantly.…”
Section: Introductionmentioning
confidence: 99%
“…They found an increase in total liver volume, with an increase in cellular and interstitial volumes but no significant change in sinusoidal volume. Furthermore, intrahepatic portal resistance of the perfused liver and portal pressure in vivo (Mastai et al, 1989) were not significantly modified. Finally, administration of alcohol, in CCl4-induced cirrhotic rats, did not further increase portal pressure measured in vivo in conscious animals, in spite of a significant increase in liver cell volume assessed by morphometry (Huet et al, unpublished data).…”
Section: Intrahepatic Portal Resistancementioning
confidence: 82%
“…The main point of contention appears to center on the validity of the measurement of portal pressure using the intrahepatic pressure method that we used in our studies. This doubt is based on the study by the Montreal group previously published in Hw.4v)i.om ( 1 ). We wish to note that the findings in such a study are at variance with those reported in the literature by seven other groups (2-7, Gibson PR, HEPAWIAX;Y 1988;8: 1723, Correspondence) that, when combined, yield a mean correlation between intrahepatic and portal pressures of r = 0.91 2 0.05 (S.D.)…”
Section: Liver Unit Andre-viallet Clinical Research Center H6pital Samentioning
confidence: 99%
“…Blendis and Israel regarding our paper on "the rat liver microcirculation in alcohol-induced hepatomegaly" ( 1 ) .…”
mentioning
confidence: 99%